Toddlers Selectively Help Fair Agents - Surian, Luca; Franchin, Laura (Frontiers in Psychology, 2017)
Previous research showed that infants and toddlers are inclined to help prosocial agents and assign a positive valence to fair distributions. Also, they expect that positive and negative actions directed towards distributors will conform to reciprocity principles. This study investigates whether toddlers are selective in helping others, as a function of others' previous distributive actions. Toddlers were presented with real-life events in which two actresses distributed resources either equally or unequally between two puppets. Then, they played together with a ball that accidentally fell to the ground and asked participants to help them to retrieve it. Participants preferred to help the actress who performed equal distributions. This finding suggests that by, the second year, children's prosocial actions are modulated by their emerging sense of fairness.